2016
DOI: 10.1038/ncomms11089
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based biomarkers of age-associated epigenetic changes in human islets associate with insulin secretion and diabetes

Abstract: Aging associates with impaired pancreatic islet function and increased type 2 diabetes (T2D) risk. Here we examine whether age-related epigenetic changes affect human islet function and if blood-based epigenetic biomarkers reflect these changes and associate with future T2D. We analyse DNA methylation genome-wide in islets from 87 non-diabetic donors, aged 26–74 years. Aging associates with increased DNA methylation of 241 sites. These sites cover loci previously associated with T2D, for example, KLF14. Blood-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
164
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(182 citation statements)
references
References 70 publications
12
164
4
2
Order By: Relevance
“…It should be noted that, although both groups included obese women, the insulin-resistant group had a significantly higher BMI and greater waist circumference compared with the more insulin-sensitive group. There has been an increasing interest in linking epigenetic signatures in human tissues to those in blood cells, to potentially identify blood-based epigenetic biomarkers that predict disease [7]. In the present study, the authors examined whether the epigenetic pattern in peripheral blood mononuclear cells (PBMCs) mirrors DNA methylation in adipose tissue and could potentially be used as a marker for insulin resistance.…”
Section: Dnmt Dna (Cytosine-5)-methyltransferase Pbmc Peripheral Bloomentioning
confidence: 99%
“…It should be noted that, although both groups included obese women, the insulin-resistant group had a significantly higher BMI and greater waist circumference compared with the more insulin-sensitive group. There has been an increasing interest in linking epigenetic signatures in human tissues to those in blood cells, to potentially identify blood-based epigenetic biomarkers that predict disease [7]. In the present study, the authors examined whether the epigenetic pattern in peripheral blood mononuclear cells (PBMCs) mirrors DNA methylation in adipose tissue and could potentially be used as a marker for insulin resistance.…”
Section: Dnmt Dna (Cytosine-5)-methyltransferase Pbmc Peripheral Bloomentioning
confidence: 99%
“…The remaining 39 loci are allocated to 26 genes (Table 1). Many of these loci have been previously described as being either expressed or methylated in an age‐related or disease‐related manner in other tissues12, 13 or as being affected in lung cancer 14. The 39 loci were significantly enriched for DNase I hypersensitive sites (DHS, OR = 5.541, RR = 5.540, p < 0.0001; chi‐square test) and known differentially methylated regions (DMR, OR = 8.873, RR = 8.869, P < 0.0001) according to array annotation, suggesting a possible role in gene regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from biochemical factors, epigenetic variations in islets [22] or alteration of DNA methylation are required to be considered for risk prediction in type 2 diabetes mellitus. Recent genome-wide study in islets revealed that a number of type 2 diabetes mellitus (T2DM) associated genes increased the levels of DNA methylation during aging and some of these genes play a role in the insulin secretion and development of T2DM [23]. For instance, it has been found that ZNF518B gene locus is gaining of DNA methylation as individuals are getting older and the higher level of DNA methylation negative correlates with the expression of this gene.…”
Section: Discussionmentioning
confidence: 99%